The fight against corruption : case study of Russia and Estonia - Belyakova, Elena; Vymětal, Petr; Dvořáková, Vladimíra, 1957-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
The purpose of this paper is to provide insight into the problem of the corruption, particularly in the Russian Federation and the Republic of Estonia, with respect to history, changes in the domestic policies as well as the situation in the world arena. Taking into consideration the common history of Russia and Estonia, it makes this topic is interesting to see how, after the collapse of the USSR, different choices and hence paths affected the corruption level and lifestyle of people. And if USSR played a role in it as well. After analysis, it will be possible to make a conclusion about the current situation and propose some solutions on how to start changing a thing by looking at the best practices in the face of countries, which now are leaders in fighting corruption.
Vedoucí práce: Petr Vymětal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses